Analysis of Business Law Approaches in Realizing Public Information Openness in Muhammadiyah Universities - A Basuki Babussalam; Asis Asis; Samsul Arifin (Universitas Internasional Batam, 2023)
Public information disclosure in Muhammadiyah universities has become a very important issue in today's digital era. This study wants to analyze and compare business law approaches in ensuring public information disclosure in the Muhammadiyah education environment. In this study, it also adopts a socio-legal/interdisciplinary approach involving legal, information technology, and information management perspectives to understand the impact and benefits of public information disclosure in the context of Muhammadiyah universities in the increasingly complex digital era. This research involves a comparative analysis of the business law approach used in ensuring public information disclosure in Muhammadiyah universities with approaches used in other educational institutions. The results showed that Muhammadiyah universities have made significant steps in improving public information openness, especially in adopting advanced information technology and information management. However, there are challenges that need to be addressed, including the need to ensure compliance with applicable laws and regulations, personal data protection, and building a culture of transparency and accountability across institutions.